Avaliação do efeito do histórico de cisalhamento na curva de escoamento de óleos parafínicos - Legnani, Amanda (2019)
Waxy crude oil has a complex composition due to the several components present in the material, such as resins and asphaltenes, which affect the material rheological behavior at low temperatures. It is well known in the literature that waxy oils are thermal and shear history dependents. In addition, some authors have shown that the flow curve of waxy oil is a function of the higher shear rate experienced by the material. In other words, the material does not recover its initial structure at rest or when a lower shear rate is applied in the sample, therefore waxy oil cannot be defined as thixotropic material. In the present work, the effect of shear history on the flow curve of the waxy oil is studied by performing experiments with controlled shear rate on rotational rheometers. This work consists of six steps, the first one is the investigation of the material steady state condition based on rheometric experiments imposing different levels of shear rate during distinct periods. One can observes that the steady state condition depends on the combination of the shear rate and the time in which it is imposed, that is the total deformation imposed on the material. For the subsequent steps of the work it was elaborated experimental protocols in which shear rate ramps followed by shear rate plateaus levels were applied in order to study the influence of the shear history on the material flow curve. It was noted that the maximum shear rate and the time that this shear rate is imposed in the material affect the apparent fluid viscosity. Therefore, by analyzing the results, one can conclude that the total deformation experienced by the material is the main point to determine the influence of the shear history on the rheological behavior of waxy oils.